Efektivitas Media Pembelajaran Tapak Gunung Berbasis Problem Based Learning Terhadap Hasil Belajar KPK dan FPB Siswa Kelas IV SD - Putri Ardia Rahma; Wahid Ibnu Zaman; Ika Santia (Universitas Islam Nahdlatul Ulama Jepara, 2026)
This study was motivated by the low student learning outcomes regarding the topics of Greatest Common Divisor (GCD) and Least Common Multiple (LCM), a result of the limited use of engaging and interactive learning media. The study aimed to determine the effectiveness of the Tapak Gunung learning media based on the Problem Based Learning (PBL) model in teaching GCD and LCM to fourth grade elementary school students. This research is part of a broader Research and Development (R&D) project for the Tapak Gunung learning media. This article focuses on the media effectiveness testing phase, employing a quantitative approach with a pre-experimental, one-group pretest-posttest design. The research subjects consisted of 32 fourth-grade students from SDN 1 Nglaban, selected using a total sampling technique. The effectiveness test was conducted in two stages: a limited trial involving 9 students and an extensive trial involving 23 students. Data were analyzed using classical learning mastery, N-Gain scores, normality tests, and paired-sample t-tests. The research instrument was a learning achievement test validated by subject matter and instructional experts. The results showed that classical learning mastery reached 88.8% in the limited trial and rose to 100% in the extensive trial. The average pretest score of 65.78 increased to 92.21 in the posttest, with an N-Gain score of 0.77, falling into the high category. The paired-sample t-test yielded a significance value of 0.000 (p < 0.05), indicating a significant difference between pretest and posttest scores. Thus, the PBL-based Tapak Gunung learning media proved effective in improving the learning outcomes of fourth-grade elementary school students regarding GCD and LCM. This medium can serve as an alternative for elementary school teachers to create mathematics instruction that is more active, engaging, and meaningful.